Roles of multiple promoter elements of the proliferating cell nuclear antigen gene during Drosophila development. - Yamaguchi, M.; Hirose, F.; Matsukage, A. (Genes to cells : devoted to molecular & cellular mechanisms, 1996)
The expression of genes involved in DNA replication is closely correlated with the proliferating state of cells and is repressed with the progression of differentiation during development. Promoter regions of the Drosophila proliferating cell nuclear antigen (PCNA) gene and the DNA polymerase alpha gene contain a common 8-base pair promoter element (DRE: DNA replication-related element). The examination of a common expression mechanism for DNA replication-related genes, which is regulated positively by growth signals and negatively by differentiation signals would be of interest. We generated PCNA-LacZ fusion genes in which the 5'-flanking sequence of the PCNA gene has been mutated. An examination of the expression of these fusion genes, introduced into flies by germ-line transformation, led to the identification of another distinct regulatory element, URE (upstream regulatory element), within the region from -168 to -119 with respect to the transcription initiation site. During embryogenesis, the region containing the DRE sequence (-108 to -91) greatly stimulated the PCNA gene minimal promoter (-86 to +130), when it was placed upstream of the promoter in both normal and reverse orientations. Addition of the URE sequence further stimulated the promoter activity twofold. During larval stages, both DRE and URE were indispensable to the promoter activity, since neither of the sequences alone activated the minimal promoter. Demonstration of beta-galactosidase activity indicated URE plays an essential role in various larval tissues such as salivary gland and imaginal disc. While the minimal promoter region alone directed maternal expression of lacZ in ovaries of adult females, both DRE and URE further stimulated promoter activity. These results show several elements of the PCNA gene promoter play roles during Drosophila development.